In Vivo Emergence of UL56 C325Y Cytomegalovirus Resistance to Letermovir in a Patient with Acute Myeloid Leukemia after Hematopoietic Cell Transplantation - Jochen J Frietsch; Detlef Michel; Thomas Stamminger; Friederike Hunstig; Sebastian Birndt; Ulf Schnetzke; Sebastian Scholl; Andreas Hochhaus; Inken Hilgendorf (Mediterranean Journal of Hematology and Infectious Diseases, 2019)
CMV associated tissue-invasive disease is associated with a considerable risk of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). Recently, the terminase inhibitor letermovir (LMV) has been approved for prophylaxis of CMV infection in HSCT. We hereby report a 60-year-old female experiencing CMV reactivation after HSCT in a CMV seronegative donor-constellation. Due to ongoing elevated CMV viral load and drug-associated myelosuppression, which prevented ganciclovir therapy, treatment was replaced by foscarnet. Due to nephrotoxicity, foscarnet was switched to LMV. The patient developed skin GvHD and prednisolone was started. Subsequently, CMV viremia worsened despite LMV therapy. Genotyping revealed the mutation C325Y of the CMV UL56 terminase being associated with high-level resistance against LMV. Prolonged uncontrolled low-level viremia due to prednisolone treatment may have favored the selection of drug-resistant CMV. Despite the excellent toxicity profile of LMV, physicians should be aware of risk factors for the emergence of resistance.